Improved Singlet Oxygen Production by Synergistic Effect via a Dual-Core Photosensitizer Doped Polymer Fibrous Films: Synthesis and Performance - Zhao, Ming; Liu, Cheng; Shan, Zhihao; Ji, Changqing; Lu, Xiaozhong; Lv, Guanglei (Frontiers in Chemistry, 2022)
Singlet oxygen (1O2) is a common reactive oxygen species which has found wide application in waste water processing, photochemical synthesis and photodynamic therapy. In this paper, a dual-metal-core (a Re(I)-based component and a Gd(III)-based component) photosensitizer was synthesized and doped into polymer fibrous films for 1O2 generation. Here the Re(I)-based component is responsible for the photosensitizing reaction which directly transformed 3O2 to 1O2, while the Gd(III)-based component served as an auxiliary part which assisted the transformation from 3O2 to 1O2 via synergistic effect by its triplet excited ligands. The photophysical parameters of this photosensitizer (denoted as Re-Gd) and its fibrous films (denoted as Re-Gd@PVP) were carefully recorded, discussed and compared. It was found that the excited state lifetime and photostability of Re-Gd were both improved after being doped into fibrous films, favoring 1O2 generation. The 1O2 generation performance comparison between Re-Gd in solid state, in solution and in fibrous films suggested that 1O2 generation performance was indeed improved by the electrospinning films. In addition, the positive factor of synergistic effect on improving 1O2-producing efficiency was confirmed by comparing Re-Gd@PVP films with reference films with a single-metal-core photosensitizer having no synergistic effect.